2017
DOI: 10.18632/oncotarget.16571
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of white blood cell, neutrophil, neutrophil-to-lymphocyte ratio, and lymphocyte-to-monocyte ratio in patients with primary angle closure glaucoma

Abstract: ObjectiveInflammatory mechanisms may have a role in the pathogenesis of primary angle closure glaucoma (PACG). The objective of this study was to investigate the diagnostic value of white blood cell (WBC), neutrophil, neutrophil to lymphocyte ratio (NLR), and lymphocyte to monocyte ratio (LMR) in patients with PACG and its association with glaucoma severity.MethodThe study was retrospectively assessed in 771 consecutive PACG patients and 770 control subjects, laboratory parameters and clinical parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 40 publications
3
35
0
2
Order By: Relevance
“…For example, Duvesh et al [30] reported significantly higher IL-8, eotaxin, IP-10 (p < 0.001) and macrophage inflammatory protein-1-beta levels in the aqueous humour of chronic PACG patients when compared to the controls. Li et al [3] suggested that the mean neutrophil, neutrophil to lymphocyte ratio and WBC values were higher in the PACG patients than in the healthy controls and that they were the lowest in the mild PACG group, followed by the moderate and severe groups. It is worth noting that a state of inflammation has been regarded as an important RDW determinant [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Duvesh et al [30] reported significantly higher IL-8, eotaxin, IP-10 (p < 0.001) and macrophage inflammatory protein-1-beta levels in the aqueous humour of chronic PACG patients when compared to the controls. Li et al [3] suggested that the mean neutrophil, neutrophil to lymphocyte ratio and WBC values were higher in the PACG patients than in the healthy controls and that they were the lowest in the mild PACG group, followed by the moderate and severe groups. It is worth noting that a state of inflammation has been regarded as an important RDW determinant [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms leading to glaucomatous atrophy in PACG cases are not fully understood, several mechanisms have been suggested. For example, inflammation [3], microangiopathy [4][5][6][7][8][9] and oxidative stress [10,11] are all currently being discussed in terms of the leading factors causing PACG, which can damage the optic nerve and lead to the progressive loss of retinal ganglion cells and their axons.…”
Section: Introductionmentioning
confidence: 99%
“…The NLR is also a new indicator for several inflammation-related ocular diseases. The NLR can be used as a novel biomarker in primary open-angle glaucoma, and WBC counts have diagnostic value in patients with primary angle-closure glaucoma (18,19). Kurtul et al (20) reported that NLR is a simple, inexpensive, and reliable prognostic biomarker for age-related macular degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical laboratory markers of systemic inflammatory status derived from complete blood count (CBC), including the neutrophil-to-lymphocyte ratio (NLR), plateletto-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), and the systemic immune inflammation index (SII), have been proposed as prognostic indicators in several diseases, including myocardial infarction, diabetes mellitus, pancreatitis, and cancer [11][12][13][14][15][16]. Evaluation of those markers in primary angle closure glaucoma, retinal vein occlusion, age-related macular degeneration, diabetic retinopathy, keratoconus, pseudoexfoliation syndrome, and pseudoexfoliation glaucoma has also suggested their potential roles as biomarkers and predictors of prognosis in ocular diseases [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%